CrevDEM: Tools for extracting crevasse location and volume from high-resolution digital elevation models. - Chudley, Thomas Russell (Zenodo, 2024)
crevdem is a Python package for extracting crevasse location and volume from high-resolution Digital Elevation Models (DEMs) of glaciers and ice sheets provided by the ArcticDEM and REMA projects. This version deposited in the repository (v0.1.0) is the version affiliated with the published paper: Chudley, T. R., Howat, I. M., King, M. D., & MacKie, E. J. (accepted). Increased crevassing across accelerating Greenland outlets. Nature Geoscience . Preprint: doi.org/10.31223/X58099. Documentation, as well as ongoing updates and maintenance, will be available from the live github repo available at https://github.com/trchudley/crevdem. Warning: These tools are designed for scientific purposes only. ArcticDEM and REMA strips are not suitable for detecting metre-scale and snow-covered crevasses, and should not be used for field hazard assessment.